2011
DOI: 10.1530/erc-10-0334
|View full text |Cite
|
Sign up to set email alerts
|

The role of somatostatin and dopamine D2 receptors in endocrine tumors

Abstract: Somatostatin (SS) and dopamine (DA) receptors have been highlighted as two critical regulators in the negative control of hormonal secretion in a wide group of human endocrine tumors. Both families of receptors belong to the superfamily of G protein-coupled receptors and share a number of structural and functional characteristics. Because of the generally reported high expression of somatostatin receptors (SSTRs) in neuroendocrine tumors (NET), somatostatin analogs (SSA) have a pronounced role in the medical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 167 publications
(159 reference statements)
1
52
0
2
Order By: Relevance
“…The development of certain small molecules with a high specificity for DR2 or knockdown of DR2 may confer an improved therapeutic prognosis (34,36). However, the DR2 agonist bromocriptin has inhibited proliferation in MCF-7 breast cancer cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…The development of certain small molecules with a high specificity for DR2 or knockdown of DR2 may confer an improved therapeutic prognosis (34,36). However, the DR2 agonist bromocriptin has inhibited proliferation in MCF-7 breast cancer cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…Thioridazine is an antagonist of the dopamine receptor D2 family proteins, and analogues of thioridazine have also exhibited antitumor effects (15), implying the involvement of the dopamine receptor signaling pathway in cancer. Dopamine receptor family proteins have been reported to be correlated with cancer therapy (20,21). Thioridazine may elicit tumor growth inhibition in a dopamine receptor-dependent and -independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PRL secretion is the most well-known action of dopamine in the anterior pituitary. However, results of recent studies have indicated that the D2 receptor is expressed in 80% of corticotrope adenomas (Lamberts et al 1980, Pivonello et al 2004, Gatto & Hofland 2011. The D2 receptor is not negatively regulated by cortisol (de Bruin et al 2009).…”
Section: Dopamine Agonistsmentioning
confidence: 99%